Principles and criteria of sustainable fashion in scientific discourse: A contemporary Ukrainian context - Soloviy, Iryna (Art and Design, 2025)
The process of change in fashion based on sustainability principles necessitates a re-evaluation of design practices, production approaches, clothing use, and attitudes towards fashion as a whole. However, a question arises as to whether the declared shift towards sustainable fashion is consistently reflected in the activities of designers and brands that position themselves as sustainable. In other words, what criteria should be used to identify the sustainability of a brand. This study aimed to determine the key aspects of scientific discourse on sustainable fashion based on clearly defined principles and criteria. The research employed a comprehensive approach, incorporating synthesis, comparative analysis of scientific literature, a review of reports and expert assessments, as well as an examination of practical cases involving Ukrainian clothing brands implementing sustainability principles. The fundamental principles and criteria of sustainable fashion have been identified. It has been observed that through the adaptation and interpretation of global sustainable fashion principles, Ukrainian designers have demonstrated unique approaches to utilising local materials, reviving and supporting traditional crafts. This has contributed to the creation of distinctive, high-quality products that align with both the functional and emotional durability of clothing. Specific sustainability assessment criteria for the local market have been identified, including the use of local materials and production, the integration of traditional craftsmanship elements, the adaptation of design to local needs, support for local educational initiatives, and the contextualisation of global standards. The implementation and application of clearly defined criteria, scientifically grounded approaches, and international standards will facilitate a high level of compliance with contemporary sustainability requirements in the fashion industry.